Risk Prediction Models for Head and Neck Cancer in the US Population From the INHANCE Consortium. Issue 4 (29th November 2019) - Lee, Yuan-Chin Amy; Al-Temimi, Mohammed; Ying, Jian; Muscat, Joshua; Olshan, Andrew F; Zevallos, Jose P; Winn, Deborah M; Li, Guojun; Sturgis, Erich M; Morgenstern, Hal; Zhang, Zuo-Feng; Smith, Elaine; et al.
Abstract: Head and neck cancer (HNC) risk prediction models based on risk factor profiles have not yet been developed. We took advantage of the large database of the International Head and Neck Cancer Epidemiology (INHANCE) Consortium, including 14 US studies from 1981–2010, to develop HNC risk prediction models. Seventy percent of the data were used to develop the risk prediction models; the remaining 30% were used to validate the models. We used competing-risk models to calculate absolute risks. The predictors included age, sex, education, race/ethnicity, alcohol drinking intensity, cigarette smoking duration and intensity, and/or family history of HNC. The 20-year absolute risk of HNC was 7.61% for a 60-year-old woman who smoked more than 20 cigarettes per day for over 20 years, consumed 3 or more alcoholic drinks per day, was a high school graduate, had a family history of HNC, and was non-Hispanic white. The 20-year risk for men with a similar profile was 6.85%. The absolute risks of oropharyngeal and hypopharyngeal cancers were generally lower than those of oral cavity and laryngeal cancers. Statistics for the area under the receiver operating characteristic curve (AUC) were 0.70 or higher, except for oropharyngeal cancer in men. This HNC risk prediction model may be useful in promoting healthier behaviors such as smoking cessation or in aiding persons with a family history of HNC to evaluate their risks.